(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To analyze factors associated with preoperative patient preparation performed by nurses at the Surgical Department, Vinmec Times City International Hospital. Methods: A cross-sectional analytical study was conducted at the Surgical Department of Vinmec Times City International Hospital from January to June 2024. The study included 184 surgical patients who were prepared preoperatively by nurses. Data were collected using a checklist evaluating five groups of standardized preoperative preparation activities. Data were analyzed using SPSS version 20.0, employing descriptive statistics and Chi–square (χ²) tests to determine associations between variables, with a significance level of p < 0.05. Results: Overall, 70.1% of nurses performed good-quality preoperative patient preparation, while 29.9% were rated as fair. All nurses achieved good performance in assessing vital signs and physical status (100%), with other preparation aspects ranging from 83.7% to 95.7%. Statistically significant associations were found between preparation outcomes and patients’ occupation, comorbidities, diagnosis, type of surgery, and form of surgery (p < 0.05). Additionally, nurse-related factors such as age, educational level, and years of experience were significantly associated with better preparation outcomes (p < 0.05), whereas gender differences were not statistically significant (p = 0.210). Conclusion: Factors significantly associated with nurses’ preoperative patient preparation included nurses’ age, educational level, and work experience, as well as patients’ occupation, comorbidities, diagnosis, type, and form of surgery.